Arterial variations of upper limb: a case report - V R Vollala; M Rao; Prasad Deepthinath (Indian Journal of Plastic Surgery)
Variations of upper limb arteries are common and there are many reports about this subject. We report multiple variations in arterial pattern of upper extremity, which were encountered in a single cadaver.